2018
DOI: 10.29252/arakmu.12.1.33
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial Activity of New Substituted Phenylthiazole Derivatives

Abstract: Background: In this study, we evaluated antibacterial and antifungle activity of these derivatives against gram positive (Staphylococcus aureus, Bacillus subtilis, B. cereus), gram negative (Proteus vulgaris) bacteria and fungale (Candida albicans, C. tropicalis and C. glabrata).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Therefore, it can be concluded that in this molecule and generally similar molecules with this structure, the presence of the naphthol moiety adjacent to the thiadiazole ring significantly increases the antimicrobial power and exerts a synergistic effect. The result obtained in this research can play a key role in the synthesis of 16) 200 ( 16) 200 (12) 4b 400 ( 13) 800 ( 16) 400 ( 13) 400 (12) 4c 800 ( 17) 400 ( 25) 400 ( 13) 400 (15) 4d 100 ( 25) 100 ( 25) 50 ( 25) 100 (17) 4e 400 ( 15) 200 ( 25) 200 ( 16) 200 (16) 4f 400 ( 25) 400 ( 18) 200 ( 16) 200 (18) 4g 400 ( 15) 800 ( 25) 200 ( 16) 800 (12) Fluconazole 200 ( 15) 100 ( 17) 200 ( 16) 200 ( 14)…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Therefore, it can be concluded that in this molecule and generally similar molecules with this structure, the presence of the naphthol moiety adjacent to the thiadiazole ring significantly increases the antimicrobial power and exerts a synergistic effect. The result obtained in this research can play a key role in the synthesis of 16) 200 ( 16) 200 (12) 4b 400 ( 13) 800 ( 16) 400 ( 13) 400 (12) 4c 800 ( 17) 400 ( 25) 400 ( 13) 400 (15) 4d 100 ( 25) 100 ( 25) 50 ( 25) 100 (17) 4e 400 ( 15) 200 ( 25) 200 ( 16) 200 (16) 4f 400 ( 25) 400 ( 18) 200 ( 16) 200 (18) 4g 400 ( 15) 800 ( 25) 200 ( 16) 800 (12) Fluconazole 200 ( 15) 100 ( 17) 200 ( 16) 200 ( 14)…”
Section: Discussionmentioning
confidence: 66%
“…Since the synthesis and evaluation of antimicrobial activity is an important part of our research program (14)(15)(16), in this study, we aimed to evaluate the antibacterial and antifungal activity of these derivatives against some microorganisms that cause the largest number of infections and, in some cases, have exhibited resistance to currently available antibiotics such as Methicillin-resistant Staphylococcus, Staphylococcus aureus, Streptococcus pyogenes, Pseudomonas aeruginosa, Escherichia coli, Candida albicans, Candida tropicalis, Candida krusei, and Candida glabrata.…”
Section: Introductionmentioning
confidence: 99%